A matching mechanism for public cloud manufacturing platforms using intuitionistic Fuzzy VIKOR and deferred acceptance algorithm. Issue 2 (3rd April 2021) - Delaram, Jalal; Fatahi Valilai, Omid; Houshamand, Mahmoud; Ashtiani, Farid
ABSTRACT: Online manufacturing platforms are spreading in the manufacturing industry in the shade of Cloud Manufacturing systems. The paper manipulates a matching mechanism for public Cloud Manufacturing platforms based on the Intuitionistic Fuzzy Sets Theory, VIKOR method, and Deferred Acceptance algorithm. The VIKOR method provides a rational, scientific, and systematic approach to enable providers and consumers to evaluate the attributes of each other and develop their preference lists. The method is augmented by the Intuitionistic Fuzzy Sets Theory to grasp the high level of vagueness and uncertainty in the process of preference list development. The utilization of Deferred Acceptance algorithm from matching games augmented the proposed mechanism for presenting stable pairs of manufacturing partners. Also, the paper studies the influence of proposer, matching algorithm, and ranking method on the mechanism. Finally, the paper presents some managerial insights, concludes the results, and states future research directions.